Perubahan Teknologi Pembelajaran - Imanuel Tenau (Jurnal Syntax Admiration, 2024)
The purpose of this study is to examine the impact of the development of information and communication technology on individual awareness of their identity, focusing on shifts in the way they think, behave, the language used, and the values held. The spread of the Covid-19 virus has changed life in the Land of Papua, including education. Although evenly distributed, this virus forced a paradigm shift in learning from face-to-face to online. While this leap has been easier for generations growing up in the digital age, older teachers have had to adjust. Primary education, especially in rural areas, faces extra challenges with the operational needs of networks and the lack of teaching online pedagogy. Parents at the elementary level helped, but not all were able to provide good support, some even made poems so that the pandemic would soon pass. Middle and high school teachers find it difficult to transform affective aspects through online learning, pointing to intergenerational challenges and significant changes in the education system. This research uses qualitative methods with phenomenological research types. Phenomenon study is a data collection technique by collecting and analyzing phenomena that occur. Phenomena are observed, interviewed then analyzed, compared and combined (synthesis) to form a systematic, integrated and complete study.